2002
DOI: 10.1034/j.1600-051x.2002.291103.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability of cultured periodontal pocket epithelium cells and Porphyromonas gingivalis association

Abstract: This study indicates that dead pocket epithelium cells harbor more P. gingivalis cells, and that a positive correlation exists between contact time and cell death. For the P. ginigvalis species, non-encapsulated strains associate in higher number. As a result, the damage they cause to the host cell seems to occur faster than occurs in encapsulated strains. As such, cell death can be seen as the end-result of bacterial association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Periodontal bacteria were incubated with H400 cells at a concentration of 1 × 10 9 ml (equivalent to approximately 100 bacteria per epithelial cell) for 1 h. This ratio of bacteria (1 : 100, epithelial cell to bacteria) was comparable with previous studies which indicate the maximum number of bacteria associated with epithelial cells in the periodontal pocket, thereby providing clinical relevance. 17 Cells or supernatants were analysed subsequently for NF-κB nuclear translocation by high content analysis, gene expression by sq-RTPCR and IL-8 protein by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…Periodontal bacteria were incubated with H400 cells at a concentration of 1 × 10 9 ml (equivalent to approximately 100 bacteria per epithelial cell) for 1 h. This ratio of bacteria (1 : 100, epithelial cell to bacteria) was comparable with previous studies which indicate the maximum number of bacteria associated with epithelial cells in the periodontal pocket, thereby providing clinical relevance. 17 Cells or supernatants were analysed subsequently for NF-κB nuclear translocation by high content analysis, gene expression by sq-RTPCR and IL-8 protein by ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were performed between passages 4 and 20 using subconfluent monolayers exposed to either 1 × 10 9 heat‐killed bacteria (approximately 100 bacteria per epithelial cell; data not shown), 10 or 20 µg E.coli LPS (Sigma) per ml of culture media, or culture media alone (control) for the times stated. The ratio of bacteria to epithelia cells used in this study was based on previous analyses [29], which have indicated the maximum number of periodontal bacteria that may associate with epithelial cells from within the periodontal pocket. This approach therefore potentially enables physiological relevance for our studies with regard to periodontitis.…”
Section: Methodsmentioning
confidence: 99%
“…The World Workshop in Periodontics reported that there is sufficient evidence to incriminate Porphyromonas gingivalis , Tannerella forsythia (previously T. forsythensis ), and Aggregatibacter actinomycetemcomitans (previously Actinobacillus actinomycetemcomitans ) as causative factors for periodontitis 1 . Studies 10–12 showed that strains of A. actinomycetemcomitans and P. gingivalis are capable of invading epithelial cells derived from human epithelial periodontal pockets or gingival sulci. A. actinomycetemcomitans also produces leukotoxin that lyses polymorphonuclear leukocytes and monocytes, which enables it to evade the innate defense line of the periodontal pocket 13 .…”
mentioning
confidence: 99%